A TINJAUAN TEORI KONSELING PADA PRAKTIK PERJODOHAN DAN DAMPAKNYA TERHADAP POTENSI KDRT - Afrilian, Andre (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2023)
Matchmaking is a practice that has precedents in Islam. It is widely practiced by the community in an effort to marry off children to someone who is considered to be well known. However, many of these arranged marriages lead to negative outcomes in the form of domestic violence due to the difficulty in adjusting to a new person who is not personally known, counseling theory becomes the main focus in efforts to understand and handle this problem. Utilizing a counseling approach, this article investigates the relationship between disagreement in arranged marriages and increased risk of domestic violence. Through a literature review, case studies, and theoretical analysis, the article discusses counseling strategies that can be used to ease tensions in an arranged marriage relationship and prevent its escalation into domestic violence. In conclusion, counseling theory opens up space for a deeper understanding of the dynamics of arranged marriage and domestic violence, while providing practical guidance for effective counseling interventions in this context.